Par-delà le changement climatique, les représentations du changement environnemental : le poids de la tension entre filière et territoire dans les secteurs pastoral et viticole en Aquitaine - Marion Charbonneau; Gaëlle Deletraz; Julien Rebotier (VertigO)
In the face of growing concerns linked to climate issue in both the scientific and the political arenas, this contribution addresses the meaning and scope of environmental change for different actors involved in pastoral and wine production sectors in the Aquitaine region of France. It states that the representations of environmental change are closely linked to the specificities of agricultural sectors, the kind of professional activities (such as farming, technics, administration, among others), and the levels of intervention (from the European to the local scale). The paper compares the discourses of different actors in both production sectors. It builds on both computer-assisted and manual analysis of discourses collected during focus-groups. Drawing on a strong thematic research and a didactic presentation of the methodology, a critical epistemological statement allows addressing the apparently normal scientific demonstration process. The latter appears to be a current and conventional process in research activities, implying posterior rearrangements that are not always made visible. Results show at last how important the regulatory dimension of environmental change can be for all actors. Climatic aspects remain a marginal concern, especially in the pastoral sector. Additionally, the study critically engages with the main drivers through which public action is implemented in agriculture. Indeed, the paper stresses how relevant the organization of the productive sectors is (be it a local and place-based organization – pastoral sector ; or a more institutional and vertical one – wine production sector) in framing representations and strategies linked with environmental change.